Design and support of an online 'control' condition for the Tele‐Savvy randomized control trial: Dementia care research (research projects; nonpharmacological) / Behavioral interventions. (7th December 2020) - Nocera, Joe R; Hepburn, Kenneth; Griffiths, Patricia; Higgins, Melinda; Epps, Fayron; Brewster, Glenna S; Bonds, Kalisha; Nash, Rachel
Abstract: Background: Tele‐Savvy is a NIA‐supported randomized trial aimed to evaluate an online version of the Savvy Caregiver, an evidence‐based in‐person psychoeducation program aimed at enhancing caregivers' capacity to manage the day‐to‐day challenges of caregiving by promoting caregiving mastery and reducing caregiving distress. A critical component of the effective evaluation of this online psychoeducation program was the development of an engaging control condition ("Tele‐Savvy Healthy Living Condition"). Methods: Caregivers were randomly assigned (in a 2:2:1 ratio) to participation in Tele‐Savvy, Healthy Living condition, or waitlist control. For Tele‐Savvy and Healthy Living, groups of 5‐8 caregivers engaged in 7 weekly synchronous online groups led by a trained facilitator. Each condition incorporated daily video lessons which caregivers viewed whenever and as often as they wished. The Healthy Living control condition incorporated evidence‐based, vetted information on healthy lifestyle behaviors (e.g., NIA Go4Life; USDA ChooseMyPlate). Results: Results demonstrate that engagement of those randomized to the Healthy Living control condition was statistically equal to those in the Tele‐Savvy program (p>0.05). Engagement was assessed by comparison of percent attendance of video conference in the Healthy Living condition (74.08%) versus Tele‐Savvy (68.02%). An intermediate report on the primary outcomes of the trial indicate that, while engaging, the Healthy Living condition did not significantly impact the primary outcomes of the randomized trial. For example, CES‐D‐assessed caregiver depression significantly decreased over time for Tele‐Savvy (p=.002) with no significant changes seen in the Healthy Living condition (p=.689) nor waitlist control (p=.141). Similarly, dyadic strain significantly decreased over time for the Tele‐Savvy group (p=.012) with no significant changes for the Healthy Living condition (p=.968) nor waitlist control (p=.135). Lastly, caregiver competence significantly increased over time for the Tele‐Savvy group (p<.001) with no significant changes for the Healthy Living control group (p=.558) nor waitlist control (p=.327). Conclusion: This initial work supports the improvements seen in the Tele‐Savvy condition are attributed to the online psychoeducation intervention and not simply the attention received via video conferencing. As such, this work supports an engaging "Control" condition which may serve future trials aimed to evaluate the effectiveness of online psychoeducation programs.